On the nexus of air pollution and health expenditures: new empirical evidence - Carla Blázquez-Fernández; David Cantarero-Prieto; Marta Pascual-Sáez (Elsevier, 2019)
Objective: To analyse the impact of per capita income and environmental air quality variables on health expenditure determinants. Method: In this study, we analyse the relationship between air pollution and health expenditure in 29 OECD countries over the period 1995-2014. In addition, we test whether our findings differ between countries with higher or lower incomes. Results: The econometric results show that per capita income has a positive effect on health expenditure, but is not as statistically significant as expected when lag-time is incorporated. In addition, an anchorage effect is observed, which implies that about 80%-90% of previous expenditure explain current expenditure. Our empirical results are quite consistent between groups and when compared with the full sample. Nevertheless, there appear to be some differences when broken down by financing scheme (total, public, and private). Conclusions: Overall, our findings could be used to clarify the appropriate health expenditure level or to obtain better environmental quality and social well-being. That is, empirical support is provided on how health management and policy makers should include more considerations for the use of cleaner fuels in developed countries. Resumen: Objetivo: Estudiar el impacto que tienen la renta per cápita y las variables de calidad ambiental sobre los gastos sanitarios. Método: Analizamos la relación entre la contaminación atmosférica y el gasto sanitario en 29 países de la OCDE durante el periodo 1995-2014. Además, estudiamos si nuestros hallazgos difieren según los países (con ingresos más altos o más bajos). Resultados: Los resultados econométricos muestran que la renta per cápita tiene un efecto positivo en los gastos sanitarios, pero no tan estadísticamente significativo como se esperaba al incorporar demoras. Además, se aprecia un efecto de anclaje, el cual implica que alrededor del 80-90% de los gastos anteriores explican los actuales. Nuestros resultados empíricos son bastante concordantes entre los grupos considerados, al compararse estos con la muestra completa. Sin embargo, parecen existir algunas diferencias al desglosar por tipo de financiación (total, pública y privada). Conclusión: En general, nuestros hallazgos podrían utilizarse para esclarecer el nivel adecuado de gasto sanitario, o bien para obtener una mejor calidad ambiental y bienestar social. Es decir, se brinda apoyo empírico sobre cómo la Administración (sanitaria) y los responsables de las distintas políticas públicas deberían incluir más consideraciones para el uso de combustibles más limpios en los países desarrollados. Keywords: Air pollution, Health expenditure, Panel data, OECD, Palabras clave: Contaminación atmosférica, Gasto sanitario, Panel de datos, OCDE